Simulation Study of Elbow Characteristics at Various Operating Conditions - AHMAD ZAINAL, RAJAIE; MUSTAFA, NORRIZAL (Progress in Engineering Application and Technology, 2023)
This study was conducted to compare the 90° elbow characteristics under several operating procedures. In this study, the pipeline and the elbow will be examined in three different size of wall thickness and tested with four different operating pressure which was 10, 12, 14, and 16 bars of pressure. Every specification of piping and fittings are retrieved from the code and standards of ASME B36.10 for piping and ASME B16.9 for long radius elbow. The pipe sizing that are chosen for this simulation study was 1.5 inch and the idea of pipeline selected are taken from Biodiesel Pilot Plant in UTHM, Parit Raja Campus which are from the outlet of fire-tube boiler to the steam header. The pipeline selected consist of two flanges, two 90° elbow and three different lengths of pipeline. The pipe material that used in Biodiesel Pilot Plant are A53 B carbon steel pipe and the working fluid was steams which the temperature design is 250℃, and the maximum operating pressure of fire tube boiler is 10 bar of pressure. This study also focused on the evaluation of the elbow performance by using simulation by using Ansys Fluent. The model of pipeline selected are designed by using Solid Work 2019 software which will be transfer to Ansys Fluent for simulation testing based on the objective that have been set. The entire model will be tested by using Ansys fluent and Ansys Mechanical to determine the stress and structural behavior after tested with different operating pressure. At the end of this study, it was confirmed that the specification of the pipeline was not compatible to run for high operating pressure. The dimensions of the 90 degrees elbow were totally affected after going through the pressure conditions setup and the size of wall thicknesses was not play the role of decreasing the value of stress and strain of the elbow. From the analysis, it was also confirmed that the elbow pipe was the highest-pressure point located for flow distribution along the pipeline. From this study, simulation proved as the best way to examine the specification of material and pressure than experimental method which caused safety effect if failed.